Gastric volvulus suspected by POCUS finding in the emergency department. Issue 8 (19th August 2022) - Kitai, Yuya; Sato, Ryota; Inoue, Tetsuya
Abstract : We described a case of a man in his 90s with gastric volvulus of which point-of-care ultrasound (POCUS) contributed to a rapid diagnosis. The patient had Borchardt's triad and POCUS showed a distended and fluid-filled stomach, which allowed us to strongly suspect gastric volvulus even prior to the abdominal CT scan. Gastric volvulus is a rare but life-threatening condition that may lead to tissue ischaemia and perforation. Therefore, a prompt diagnosis is extremely important. This case suggests that POCUS can be a powerful tool when clinicians suspect gastric volvulus.